Crystallization kinetics as a sensitive tool to detect degradation in poly(lactide)/poly(ε-caprolactone)/ PCL-co-PC copolymers blends. (October 2019) - Giacobazzi, Greta; Rizzuto, Matteo; Zubitur, Manuela; Mugica, Agurtzane; Caretti, Daniele; Müller, Alejandro J.
Abstract: Poly(lactide)/poly(ε-caprolactone) blends (PLA/PCL) with composition 80/20 (w/w%) are immiscible but biodegradable and therefore often studied in the literature. We have prepared 80/20 PLA/PCL blends with and without poly(ε-caprolactone)- co -poly(carbonate) copolymers (block and random). The blends were prepared both by melt extrusion and by solution blending. The concentration of PCL- co -PC copolymers added to the blends was 2 wt%. Compression molded sheets and solvent cast films were evaluated by GPC (Gel Permeation Chromatography), TGA (Thermogravimetric Analysis), SEM (Scanning Electron Microscopy), PLOM (Polarized Light Optical Microscopy) and DSC (Differential Scanning Calorimetry). Copolymer addition causes a reduction of molecular weight in melt mixed blends. In particular, the random copolymer (PCL- ran -PC) causes the highest molecular weight reduction, since it has lower thermal stability, as shown by TGA. PLOM experiments show that these degraded PLA chains in melt-mixed blends can nucleate and grow faster than similar but undegraded PLA chains in solution-mixed blends. As a result, the PLA phase within melt mixed blends containing PCL- co -PC copolymers shows a higher tendency to crystallize during both isothermal and non-isothermal DSC experiments. Upon molecular weight reduction in melt mixed blends containing copolymers, PLA chains have a higher mobility resulting in faster diffusion towards the growing crystal front. Our results show crystallization kinetic measurements, performed by PLOM or DSC, are useful tools to qualitatively detect molecular weight changes produced by degradation of PLA chains, when the molecular weight reduction is not large enough to decrease T m values. Highlights: 80/20 PLA/PCL blends with and without PCL- co -PC copolymers were prepared. Blend preparation was performed by both solution and melt blending. In the case of melt blending the PLA component was degraded as evidenced by GPC. Both spherulitic growth and overall crystallization kinetics were very sensitive to degradation. In the Mw range employed, the melting point of PLA was insensitive to degradation.